The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4319/lo.2013.58.5.1689
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of groundwater‐derived nitrate and nitrous oxide in a tidal estuary from radon mass balance modeling

Abstract: We monitored submarine groundwater discharge (SGD) into the Werribee Estuary, Australia, using both chemical and physical methods. SGD occurred at hotspots where 222 Rn persisted through a 12 month survey period. A significant correlation between 222 Rn and NO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 58 publications
7
54
0
Order By: Relevance
“…Hwang et al (2005) reported higher fluxes of 21.4 mmol m − 2 d −1 driven by high SGD rates from Bangdu Bay on Jeju Island, Korea. In smaller estuarine systems, lower GW-derived DIN fluxes of 0.33 mmol m −2 d −1 were estimated from Pettaquamscutt Estuary, USA, likely due to a smaller groundwater nutrient reservoir in the region (Kelly and Moran, 2002) while average SGD-derived NO 3 flux from Werribee Estuary, Australia was reported to be 166 mmol m −2 d −1 , 35 fold higher than our average observations (Wong et al, 2013).…”
Section: Groundwater-derived Nutrient Inputs: Fresh Vs Salinementioning
confidence: 82%
See 2 more Smart Citations
“…Hwang et al (2005) reported higher fluxes of 21.4 mmol m − 2 d −1 driven by high SGD rates from Bangdu Bay on Jeju Island, Korea. In smaller estuarine systems, lower GW-derived DIN fluxes of 0.33 mmol m −2 d −1 were estimated from Pettaquamscutt Estuary, USA, likely due to a smaller groundwater nutrient reservoir in the region (Kelly and Moran, 2002) while average SGD-derived NO 3 flux from Werribee Estuary, Australia was reported to be 166 mmol m −2 d −1 , 35 fold higher than our average observations (Wong et al, 2013).…”
Section: Groundwater-derived Nutrient Inputs: Fresh Vs Salinementioning
confidence: 82%
“…7). Previous studies have also indicated that groundwater discharge plays an important role in delivering DIN to estuaries (Moore et al, 2006;Wong et al, 2013;Porubsky et al, 2014). In a study in the upper Gulf of Thailand, groundwater-derived DIN, DIP, DON and DOP were reported to be 40-50%, 60-70%, 30-40% and 30-130% of the fluxes delivered by the Chao Phraya River into the ocean (Burnett et al, 2007).…”
Section: Groundwater-derived Nutrient Inputs: Fresh Vs Salinementioning
confidence: 92%
See 1 more Smart Citation
“…To estimate the discharge of fresh groundwater, we adapted a mass balance approach previously applied to some estuaries and coastal seas for 222 Rn (Cable et al 1996;Hwang et al 2005;Santos et al 2010;Wong et al 2013) and salinity (Hatta and Zhang 2013). 222 Rn and salt budgets in Obama Bay are summarized in Fig.…”
Section: Mass Balance Model For 222 Rn and Salinity In Obama Baymentioning
confidence: 99%
“…SGD may be a two-fold source of N2O to surface waters. Initial investigations revealed significant fluxes of N2O associated with FSGD to an urban estuary [Wong et al, 2013] and in a coral reef lagoon where tides drive significant seawater recirculation through the aquifer [O'Reilly et al, 2015].…”
mentioning
confidence: 99%